A Sociolinguistic Perspective in Narrative Analysis: Educational Backgrounds of Families as Influential Factors in the Development of Personal Experience Child Narratives - Suhan Akıncı Oktay (Dilbilim Araştırmaları Dergisi)
This article provides a sociolinguistic framework for the analysis of personal experience narratives in terms of Labovian story structure. The study focuses on the children of two distinct groups of parents; one with higher, the other with lower socio-economic level and educational backgrounds. In this study, written narratives reflecting the personal fright experiences of 9-to-10-year-old children attending two primary schools in Ankara, representing higher parental education group and lower parental education group have been compared on the basis of Labov’s Personal Experience Narrative Analysis. The findings indicate that the children of socially and educationally better-level parents display better writing narration skills both mentally and linguistically. This finding denotes the importance of parental and environmental factors.